Study of trace elements status of breast cancer patients - Tillashaykhov, M.N; Khudaykulov, A.T.; Danilova, E.A.; Usupbekov, A.A.; Alimkhodjaeva, L.T. (Онкологія, 2017)
The
last 15
years, the methods of evaluation of trace elements in the human body
for the hair analysis have been actively developing. The content of trace elements
in hair reflects their level in the human body, and is an integral indicator charac
-
terizing his element status.
Purpose:
study of trace elements in patients with second-
stage breast cancer.
Object and Methods:
to determine the content of trace elements,
it was stu
died the hair of 30
patients with stage II breast cancer who were treated at
the Natio
nal Cancer Research Center of the Ministry of Health of the Republic of
Uzbekistan in 2016. The study of hair samples for content of trace elements (calci
-
um, potassium, sodium, chlorine, iron, zinc, copper, manganese, cobalt, chromium,
selenium, iodine, bromine) was conducted in the laboratory analysis of the activa
-
tion of the Institute of Nuclear Physics of Uzbekistan Academy of Sciences, instru
-
mental neutron activation analysis. The received data on the micronutrient content
in hair of patients compared with reference values for the population of Uzbekistan,
adopted at the Institute of Nuclear Physics.
Results:
the reduction of iron, zinc, cop
-
per, cobalt level and high content of chlorine as compared with the reference val
-
ues were showed.
Conclusions:
undertaken
studies have shown the possibility of us
-
ing of the results for the primary prevention and identification of risk groups among
women, as well as the usefulness of the correction of specialized treatment medica
-
tion with microelement complexes. Резюме.
Последние 15
лет активно развиваются ме
-
тодики оценки содержания микроэлементов (МЭ)
в организме человека по анализу волос. Содержание
МЭ в
волосах рассматривают в настоящее время
как интегральный показатель, характеризующий
элементный статус организма.
Цель работы:
изуче
-
ние содержания МЭ у больных раком молочной желе
-
зы (РМЖ) II стадии.
Объект и
методы:
исследованы
волосы 30
пациенток с РМЖ II стадии, находивших
-
ся на стационарном лечении в Республиканском онко
-
логическом научном центре Министерства здраво
-
охранения Республики Узбекистан в 2016
г. Изучение
образцов волос на содержание МЭ (кальций, калий,
натрий, хлор, железо, цинк, медь, марганец, кобальт,
хром, селен, йод, бром) проводили в лаборатории акти
-
вационного анализа Института ядерной физики Ака
-
демии наук Республики Узбекистан инструменталь
-
ным нейтронно-активационным анализом. Получен
-
ные данные о содержании МЭ в волосах пациенток
сравнивали с
референтными показателями для насе
-
ления Узбекистана, принятыми в Институте.
Ре
-
зультаты:
выявлено сниженное содержание железа,
цинка, меди, кобальта, и
повышенное хлора по
срав
-
нению с референтными значениями.
Выводы:
прове
-
денные исследования указывают на возможность ис
-
пользования данных о содержании МЭ в волосах для
первичной профилактики РМЖ и выявления групп ри
-
ска среди женщин, а также свидетельствуют о це
-
лесообразности проведения коррекции специализи
-
рованного лечения медикаментозными комплексами
с добавлением МЭ.